PELAKSANAAN KEHUMASAN DALAM PENYEBARAN INFORMASI PADA DINAS PERPUSTAKAAN DAN KEARSIPAN DI KABUPATEN BONE - Herianti, Herianti; Parawangi, Anwar; Syukri, Syukri (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aimed to find out  the implementation of public relations in disseminating information at the Library and Archives Service in Bone Regency. This study used qualitative research methods and the type of research used descriptive. Data collection techniques used observation and interviews. The results showed that the implementation of public relations in disseminating information at the Library and Archives Service in Bone Regency, showed that from four indicators of credibility, in the form of delivering information needed by the community, both direct and indirect communication. Context, education related to the problems that often occured in  society, as well as inviting and fostering children to love reading, love and make the library a fun place for learning and playing. Channels, channels that could be used by the public to access news related to information, were the official website of the village library and library service. Audience capacity, ability and skill in good and correct communication.